Targeting IL-6 receptor mediated metabolic pathways to control Th17 cell differentiation and inflammatory responses - Alwarawrah, Yazan; Nichols, Amanda G.; Patel, Isha; Ball, Andréa B.; MacIver, Nancie J. (Frontiers in Immunology, 2025)
Interleukin-6 (IL-6) is a multifunctional cytokine that plays important roles in inflammation. Several studies have shown that IL-6 regulates various aspects of T cell function, including the differentiation of CD4+ T cells into the pro-inflammatory Th17 subset. Given the tight link between T cell metabolism and function, and the role of IL-6 in regulating cellular metabolism across tissues, we investigated the role of IL-6 signaling in Th17 cell metabolism. Using T cell specific IL-6 receptor (IL-6R) conditional knockout mice and littermate controls, we found that IL-6R signaling regulates the proportions of CD4+ and CD8+ T cells and drives CD4+ T cell differentiation into Th17 cells. We also found that IL-6R signaling is required for Th17 cell glycolytic metabolism. In T cell-specific IL-6R knockout mice, Th17 cells had reduced glucose uptake and glycolysis, as well as decreased expression of key glycolytic enzymes, while showing increased basal oxygen consumption. However, we also found that IL-6R signaling enhanced oxidative capacity and mitochondrial coupling efficiency in Th17 T cells. Importantly, inhibition of lactate dehydrogenase using FX11 selectively impaired Th17 cell differentiation with minimal effects on Treg cells. These findings suggest that targeting metabolic pathways regulated by IL-6R signaling can selectively inhibit inflammatory Th17 responses, offering a potential strategy for controlling IL-6 mediated inflammation.